Gender Bias in The Indonesian Correctional System: A Legal Analysis of Human Rights Protection Gaps for Female Prisoners - Monica, Dona Raisa; Marpaung, Indra Joseph; Al Akayleh, Shaker Suleiman Ali; Maroni; Fardiansyah, Ahmad Irzal (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2025)
The correctional system in Indonesia is designed to rehabilitate prisoners humanely, without discrimination. However, in practice, female prisoners often face inequal treatment due to correctional structures and policies that are still gender biased. This article aims to analyse the gap in human rights protection for female prisoners in Indonesia through a normative legal research approach supported by empirical data, which is then analysed qualitatively. The results of the study found that although the national legal framework already includes human rights principles, in practice, female prisoners still face various structural injustices and gender bias, such as a lack of reproductive health facilities, insufficient protection from violence, and limited access to women-friendly basic services. This article concludes that there is a need for policies to guide the treatment of female prisoners and to strengthen oversight mechanisms to ensure the fulfilment of human rights for female prisoners. This study contributes to developing a more just and equitable correctional law.